INTERACTION OF MONETARY, CREDIT AND BUDGET POLICY AS A WAY TO OVERCOME CRISIS IN RUSSIA - Ivan I. Volkov (Plekhanov Russian University of Economics, 2017)
Crisis phenomena arise due to external and internal factors. In such circumstances responsibility rests on macro-economic regulators, i. e. the Bank of Russia and the Ministry of Finance. Their steps must be coordinated, as each of them has to make a controversial choice between taking crisis measures and following a strategic direction. Taking into consideration the said situation the author advances a set of procedures aimed at overcoming the adverse macro-economic tendencies. Each of these procedures implies coordination between monetary, credit and budget policy. As a result a complex of proposals was developed to overcome the crisis phenomena in Russia.